2018
DOI: 10.1111/eci.13042
|View full text |Cite
|
Sign up to set email alerts
|

Effect of honey on glucose and insulin concentrations in obese girls

Abstract: Background Childhood obesity represents a major health problem of our century. The benefits of natural products, such as honey, in the management of obesity have gained renewed interest. In this study, we investigated the effect of honey on glucose and insulin concentrations in obese prepubertal girls. Materials and Methods Thirty healthy obese girls aged 10.55 (±SEM:0.34) years with a mean body mass index (BMI) above the 97th centile for age (28.58 ± 1.40 kg/m2, BMI z‐score 2.96) underwent a standard oral glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 37 publications
(71 reference statements)
0
14
0
Order By: Relevance
“…In particular, dietary honey supplementation prevented the fasting hyperglycemia and the impairment of the glucose response during the glucose tolerance test, and it improved the plasma insulin concentration, insulin sensitivity and HOMA index, suggesting a preventive effect of the long-term honey ingestion in HFDinduced impairment of glucose homeostasis. On the other hand, honey hypoglycemic properties have been pointed out not only in diabetes rodent models but also in healthy subjects and diabetic patients [17,22,37,38]. In our experimental conditions, we did not observe any significant impact on weight gain or plasma lipid concentrations in HFD-H mice, ruling out an improvement of lipid metabolism as responsible for the observed effects on glucose metabolism.…”
Section: Discussionmentioning
confidence: 41%
“…In particular, dietary honey supplementation prevented the fasting hyperglycemia and the impairment of the glucose response during the glucose tolerance test, and it improved the plasma insulin concentration, insulin sensitivity and HOMA index, suggesting a preventive effect of the long-term honey ingestion in HFDinduced impairment of glucose homeostasis. On the other hand, honey hypoglycemic properties have been pointed out not only in diabetes rodent models but also in healthy subjects and diabetic patients [17,22,37,38]. In our experimental conditions, we did not observe any significant impact on weight gain or plasma lipid concentrations in HFD-H mice, ruling out an improvement of lipid metabolism as responsible for the observed effects on glucose metabolism.…”
Section: Discussionmentioning
confidence: 41%
“…Some of the animal studies used orlistat as a positive control (32,35). For clinical trials, the subjects involved were obese prepubertal girls (37) and obese adults (36,38). Control groups in the clinical trials were supplemented with marmalade (37) and sucrose (38).…”
Section: Experimental Modelsmentioning
confidence: 99%
“…Meanwhile, in the remaining two animal studies, the type and source of the natural honey used were not stated in the articles (34,38). The active compounds found in honey are phenols (35,37) and flavonoids (35). One study conducted gas chromatography-mass spectrometry (GC-MS) analysis of SBH and found various active compounds in SBH such as 4-hydroxyphenyl acetic acid, caffeic acid derivatives, caffeoyl hexoside derivatives, coumaric acid, gluconic acid, kynurenic acid derivatives, pinobanksin, quinic acid, niazimicin, bisosthenon B, (6β,7α,12β,13β)-7-hydroxy-11,16dioxo-8,14-apianadien-22, 6-olide, aegle marmelos alkaloid C, 7-chloro-6-demethyl cepharadione B, n-acetylglycine and lanosterol (33).…”
Section: Types Sources and Contents Of Honeymentioning
confidence: 99%
See 1 more Smart Citation
“…In a human intervention study, 30 days of 70 g of honey (collected from Iran) was reported to reduce FBG compared to overweight individuals fed with sucrose [ 88 ]. In obese girls, supplementation of 15 g honey for 6 months caused a reduction in BMI and the area under the concentration–time curve (AUC) in an oral glucose tolerance test and insulin [ 102 ]. Agrawal and colleagues observed a higher degree of tolerance to honey with a significantly lower glucose level in patients with diabetes or impaired glucose tolerance after consumption of 90 g of unprocessed natural honey from India in 300 mL of water, at a 30-min interval up to 2 h [ 103 ].…”
Section: The Mechanisms Of Honey In Reversing Metabolic Changesmentioning
confidence: 99%